Does everyone have a price? On the role of payoff magnitude for ethical decision making - Benjamin E. Hilbig; Isabel Thielmann (Cognition, 2017)
Most approaches to dishonest behavior emphasize the importance of corresponding payoffs, typically implying that dishonesty might increase with increasing incentives. However, prior evidence does not appear to confirm this intuition. However, extant findings are based on relatively small payoffs, the potential effects of which are solely analyzed across participants. In two experiments, we used different multi-trial die-rolling paradigms designed to investigate dishonesty at the individual level (i.e., within participants) and as a function of the payoffs at stake - implementing substantial incentives exceeding 100€. Results show that incentive sizes indeed matter for ethical decision making, though primarily for two subsets of “corruptible individuals” (who cheat more the more they are offered) and “small sinners” (who tend to cheat less as the potential payoffs increase). Others (“brazen liars”) are willing to cheat for practically any non-zero incentive whereas still others (“honest individuals”) do not cheat at all, even for large payoffs. By implication, the influence of payoff magnitude on ethical decision making is often obscured when analyzed across participants and with insufficiently tempting payoffs.

Borderline Personality and the Detection of Angry Faces - Johanna Hepp; Benjamin E. Hilbig; Pascal J. Kieslich; Julia Herzog; Stefanie Lis; Christian Schmahl; Inga Niedtfeld (PLOS ONE, 2016)

Dissociating Indifferent, Directional, and Extreme Responding in Personality Data: Applying the Three-Process Model to Self- and Observer Reports - Ingo Zettler; Jonas W. B. Lang; Ute R. Huelsheger; Benjamin E. Hilbig (JOURNAL OF PERSONALITY, 2016)

The Reversed Description-Experience Gap: Disentangling Sources of Presentation Format Effects in Risky Choice - Andreas Gloeckner; Benjamin E. Hilbig; Felix Henninger; Susann Fiedler (JOURNAL OF EXPERIMENTAL PSYCHOLOGY-GENERAL, 2016)

The two faces of cooperation: On the unique role of HEXACO Agreeableness for forgiveness versus retaliation - Benjamin E. Hilbig; Isabel Thielmann; Sina A. Klein; Felix Henninger (JOURNAL OF RESEARCH IN PERSONALITY, 2016)

A predominance of self-identified Democrats is no evidence of a leftward bias - Benjamin E. Hilbig; Morten Moshagen (Behavioral and Brain Sciences, 2015)

Different Games for Different Motives: Comment on Haesevoets, Folmer, and Van Hiel (2015) - Isabel Thielmann; Robert Böhm; Benjamin E. Hilbig (European journal of personality, 2015)

Dishonest responding or true virtue? A behavioral test of impression management - Ingo Zettler; Benjamin E. Hilbig; Morten Moshagen; Reinout E. de Vries (Personality and Individual Differences, 2015)

From basic personality to motivation: Relating the HEXACO factors to achievement goals - Felix C. Dinger; Oliver Dickhäuser; Benjamin E. Hilbig; Elena Müller; Ricarda Steinmayr; Linda Wirthwein (Learning and Individual Differences, 2015)

From Honesty-Humility to fair behavior - Benevolence or a (blind) fairness norm? - Benjamin E. Hilbig; Isabel Thielmann; Johanna Wührl; Ingo Zettler (Personality and Individual Differences, 2015)

From personality to altruistic behavior (and back): Evidence from a double-blind dictator game - Benjamin E. Hilbig; Isabel Thielmann; Johanna Hepp; Sina A. Klein; Ingo Zettler (Journal of Research in Personality, 2015)

Generalized outcome-based strategy classification: Comparing deterministic and probabilistic choice models (vol 21, pg 1431, 2014) - Benjamin E. Hilbig; Morten Moshagen (PSYCHONOMIC BULLETIN & REVIEW, 2015)

Honesty and Humility - Ingo Zettler; Benjamin E. Hilbig (International Encyclopedia of the Social & Behavioral Sciences, 2015)

Judging competing theoretical accounts by their empirical content and parsimony: REply to Myrseth and Wollbrant - Benjamin E. Hilbig; Pascal J. Kieslich (Judgment and decision making, 2015)

The Traits One Can Trust: Dissecting Reciprocity and Kindness as Determinants of Trustworthy Behavior - Isabel Thielmann; Benjamin E. Hilbig (PERSONALITY AND SOCIAL PSYCHOLOGY BULLETIN, 2015)

Trust: An integrative review from a person-situation perspective. - Isabel Thielmann; Benjamin E. Hilbig (Review of General Psychology, 2015)

Truth Will Out: Linking Personality, Morality, and Honesty Through Indirect Questioning - Benjamin E. Hilbig; Morten Moshagen; Ingo Zettler (SOCIAL PSYCHOLOGICAL AND PERSONALITY SCIENCE, 2015)

Whatever the cost? Information integration in memory-based inferences depends on cognitive effort - Benjamin E. Hilbig; Martha Michalkiewicz; Marta Castela; Ruediger F. Pohl; Edgar Erdfelder (MEMORY & COGNITION, 2015)

When the cat’s away, some mice will play: A basic trait account of dishonest behavior - Benjamin E. Hilbig; Ingo Zettler (Journal of Research in Personality, 2015)

Active versus reactive cooperativeness in Borderline Psychopathology: A dissection based on the HEXACO model of personality - Johanna Hepp; Benjamin E. Hilbig; Morten Moshagen; Ingo Zettler; Christian Schmahl; Inga Niedtfeld (PERSONALITY AND INDIVIDUAL DIFFERENCES, 2014)

An Experimental Validation Method for Questioning Techniques That Assess Sensitive Issues - Morten Moshagen; Benjamin E. Hilbig; Edgar Erdfelder; Annie Moritz (EXPERIMENTAL PSYCHOLOGY, 2014)

Cognitive conflict in social dilemmas: An analysis of response dynamics - Pascal J. Kieslich; Benjamin E. Hilbig (JUDGMENT AND DECISION MAKING, 2014)

Faktorenstruktur, psychometrische Eigenschaften und Messinvarianz der deutschsprachigen Version des 60-Item HEXACO Persönlichkeitsinventars - Morten Moshagen; Benjamin E. Hilbig; Ingo Zettler (Diagnostica, 2014)

Generalized outcome-based strategy classification: Comparing deterministic and probabilistic choice models - Benjamin E. Hilbig; Morten Moshagen (PSYCHONOMIC BULLETIN & REVIEW, 2014)

On the role of recognition in consumer choice: A model comparison - Benjamin E. Hilbig (JUDGMENT AND DECISION MAKING, 2014)

Personality and Prosocial Behavior: Linking Basic Traits and Social Value Orientations - Benjamin E. Hilbig; Andreas Gloeckner; Ingo Zettler (JOURNAL OF PERSONALITY AND SOCIAL PSYCHOLOGY, 2014)

Rethinking Trait Conceptions of Social Desirability Scales: Impression Management as an Expression of Honesty-Humility - Reinout E. de Vries; Ingo Zettler; Benjamin E. Hilbig (ASSESSMENT, 2014)

The impact of subjective recognition experiences on recognition heuristic use: A multinomial processing tree approach - Marta Castela; David Kellen; Edgar Erdfelder; Benjamin E. Hilbig (PSYCHONOMIC BULLETIN & REVIEW, 2014)

To boast or not to boast: Testing the humility aspect of the Honesty-Humility factor - Benjamin E. Hilbig; Timo Heydasch; Ingo Zettler (PERSONALITY AND INDIVIDUAL DIFFERENCES, 2014)

Trust in me, trust in you: A social projection account of the link between personality, cooperativeness, and trustworthiness expectations - Isabel Thielmann; Benjamin E. Hilbig (JOURNAL OF RESEARCH IN PERSONALITY, 2014)

What is adaptive about adaptive decision making? A parallel constraint satisfaction account - Andreas Gloeckner; Benjamin E. Hilbig; Marc Jekel (COGNITION, 2014)

WILLING TO GIVE BUT NOT TO FORGIVE: BORDERLINE PERSONALITY FEATURES AND COOPERATIVE BEHAVIOR - Isabel Thielmann; Benjamin E. Hilbig; Inga Niedtfeld (JOURNAL OF PERSONALITY DISORDERS, 2014)

Deliberation versus automaticity in decision making: Which presentation format features facilitate automatic decision making? - Anke Soellner; Arndt Broeder; Benjamin E. Hilbig (JUDGMENT AND DECISION MAKING, 2013)

Effort reduction after self-control depletion: The role of cognitive resources in use of simple heuristics - Ruediger F. Pohl; Edgar Erdfelder; Benjamin E. Hilbig; Lisa Liebke; Dagmar Stahlberg (JOURNAL OF COGNITIVE PSYCHOLOGY, 2013)

It takes two: Honesty-Humility and Agreeableness differentially predict active versus reactive cooperation - Benjamin E. Hilbig; Ingo Zettler; Felix Leist; Timo Heydasch (PERSONALITY AND INDIVIDUAL DIFFERENCES, 2013)

Tracing the Path from Personality - via Cooperativeness - to Conservation - Benjamin E. Hilbig; Ingo Zettler; Morten Moshagen; Timo Heydasch (EUROPEAN JOURNAL OF PERSONALITY, 2013)

Two sides of one coin: Honesty-Humility and situational factors mutually shape social dilemma decision making - Ingo Zettler; Benjamin E. Hilbig; Timo Heydasch (JOURNAL OF RESEARCH IN PERSONALITY, 2013)

What lies beneath: How the distance between truth and lie drives dishonesty - Benjamin E. Hilbig; Corinna M. Hessler (JOURNAL OF EXPERIMENTAL SOCIAL PSYCHOLOGY, 2013)

A matter of time: Antecedents of one-reason decision making based on recognition - Benjamin E. Hilbig; Edgar Erdfelder; Ruediger F. Pohl (ACTA PSYCHOLOGICA, 2012)

Good Things Don't Come Easy (to Mind) Explaining Framing Effects in Judgments of Truth - Benjamin E. Hilbig (EXPERIMENTAL PSYCHOLOGY, 2012)

Heuristics: The Foundations of Adaptive Behavior - Benjamin E. Hilbig (JOURNAL OF ECONOMIC PSYCHOLOGY, 2012)

How framing statistical statements affects subjective veracity: Validation and application of a multinomial model for judgments of truth - Benjamin E. Hilbig (COGNITION, 2012)

Processing differences between descriptions and experience: a comparative analysis using eye-tracking and physiological measures - Andreas Gloeckner; Susann Fiedler; Guy Hochman; Shahar Ayal; Benjamin E. Hilbig (FRONTIERS IN PSYCHOLOGY, 2012)

Risk is relative: Risk aversion yields cooperation rather than defection in cooperation-friendly environments - Andreas Gloeckner; Benjamin E. Hilbig (PSYCHONOMIC BULLETIN & REVIEW, 2012)

The role of subjective linear orders in probabilistic inferences - Ruediger F. Pohl; Benjamin E. Hilbig (PSYCHONOMIC BULLETIN & REVIEW, 2012)

Yes, they can! Appropriate weighting of small probabilities as a function of information acquisition (vol 138, pg 337, 2011) - Benjamin E. Hilbig (ACTA PSYCHOLOGICA, 2012)

Altruism at the ballots: Predicting political attitudes and behavior - Ingo Zettler; Benjamin E. Hilbig; Julia Haubrich (Journal of Research in Personality, 2011)

Defection in the dark? A randomized-response investigation of cooperativeness in social dilemma games - Morten Moshagen; Benjamin E. Hilbig; Jochen Musch (European Journal of Social Psychology, 2011)

Dissecting work commitment: the role of Machiavellianism - Ingo Zettler; Niklas Friedrich; Benjamin E. Hilbig (Career Dev Int, 2011)

Fluent, fast, and frugal? A formal model evaluation of the interplay between memory, fluency, and comparative judgments. - Benjamin E. Hilbig; Edgar Erdfelder; Rüdiger F. Pohl (Journal of Experimental Psychology: Learning, Memory, and Cognition, 2011)

Homo heuristicus Outnumbered: Comment on Gigerenzer and Brighton (2009) - Benjamin E. Hilbig; Tobias Richter (Topics in Cognitive Science, 2011)

Methodological notes on model comparisons and strategy classification: A falsificationist proposition - Morten Moshagen; Benjamin E. Hilbig (JUDGMENT AND DECISION MAKING, 2011)

Methodology in judgment and decision making research - Andreas Gloeckner; Benjamin E. Hilbig (JUDGMENT AND DECISION MAKING, 2011)

Personality, Punishment and Public Goods: Strategic Shifts Towards Cooperation as a Matter of Dispositional Honesty-Humility - Benjamin E. Hilbig; Ingo Zettler; Timo Heydasch (European Journal of Social Psychology, 2011)

Yes, they can! Appropriate weighting of small probabilities as a function of information acquisition - Benjamin E. Hilbig; Andreas Glöckner (Acta Psychologica, 2011)

Attitudes of the selfless: Explaining political orientation with altruism - Ingo Zettler; Benjamin E. Hilbig (PERSONALITY AND INDIVIDUAL DIFFERENCES, 2010)

Honesty-humility and a person-situation interaction at work - Ingo Zettler; Benjamin E. Hilbig (Eur. J. Pers., 2010)
Person-situation interactions have attracted researchers' attention for decades. Likewise, the current work focuses on the interaction of honesty-humility and situational conditions in bringing about counterproductive work behaviour (CWB). As such, we introduce perceptions of organizational politics as a situational construct representing an opportunity for CWB. In a sample of N = 148 employees we found that particularly individuals low in honesty-humility were affected by situational circumstances. By contrast, those high in honesty-humility reported practically the same (lower) amount of CWB independent of the level of perceptions of organizational politics. In other words, employees low in honesty-humility were especially likely to condition their behaviour on environmental factors, a result that mirrors previous findings. Copyright © 2010 John Wiley & Sons, Ltd.

One-Reason Decision Making Unveiled: A Measurement Model of the Recognition Heuristic - Benjamin E. Hilbig; Edgar Erdfelder; Ruediger F. Pohl (JOURNAL OF EXPERIMENTAL PSYCHOLOGY-LEARNING MEMORY AND COGNITION, 2010)

Precise models deserve precise measures: A methodological dissection - Benjamin E. Hilbig (JUDGMENT AND DECISION MAKING, 2010)

Reconsidering "evidence" for fast-and-frugal heuristics - Benjamin E. Hilbig (PSYCHONOMIC BULLETIN & REVIEW, 2010)

Think or blink - is the recognition heuristic an "intuitive" strategy? - Benjamin E. Hilbig; Sabine G. Scholl; Ruediger F. Pohl (JUDGMENT AND DECISION MAKING, 2010)

Criterion Knowledge: A Moderator of Using the Recognition Heuristic? - Benjamin E. Hilbig; Ruediger F. Pohl; Arndt Broeder (JOURNAL OF BEHAVIORAL DECISION MAKING, 2009)

Effects of instruction on learners' ability to generate an effective pathway in the method of loci - Cristina Massen; Bianca Vaterrodt-Pluennecke; Lucia Krings; Benjamin E. Hilbig (MEMORY, 2009)

Ignorance- Versus Evidence-Based Decision Making: A Decision Time Analysis of the Recognition Heuristic - Benjamin E. Hilbig; Ruediger F. Pohl (JOURNAL OF EXPERIMENTAL PSYCHOLOGY-LEARNING MEMORY AND COGNITION, 2009)

Multinomial Processing Tree Models A Review of the Literature - Edgar Erdfelder; Tina-Sarah Auer; Benjamin E. Hilbig; Andre Assfalg; Morten Moshagen; Lena Nadarevic (ZEITSCHRIFT FUR PSYCHOLOGIE-JOURNAL OF PSYCHOLOGY, 2009)

Pillars of cooperation: Honesty-Humility, social value orientations, and economic behavior - Benjamin E. Hilbig; Ingo Zettler (JOURNAL OF RESEARCH IN PERSONALITY, 2009)

Sad, thus true: Negativity bias in judgments of truth - Benjamin E. Hilbig (JOURNAL OF EXPERIMENTAL SOCIAL PSYCHOLOGY, 2009)

Identification and success of using or not-using the recognition heuristic - Ruediger F. Pohl; Benjamin E. Hilbig (INTERNATIONAL JOURNAL OF PSYCHOLOGY, 2008)

Individual differences in fast-and-frugal decision making: Neuroticism and the recognition heuristic - Benjamin E. Hilbig (JOURNAL OF RESEARCH IN PERSONALITY, 2008)

One-reason decision making in risky choice? A closer look at the priority heuristic - Benjamin E. Hilbig (JUDGMENT AND DECISION MAKING, 2008)

Recognizing Users of the Recognition Heuristic - Benjamin E. Hilbig; Ruediger F. Pohl (EXPERIMENTAL PSYCHOLOGY, 2008)

The influence of criterion knowledge on the recognition heuristic - Benjamin E. Hilbig; Ruediger F. Pohl; Arndt Broeder (INTERNATIONAL JOURNAL OF PSYCHOLOGY, 2008)

Journal of experimental social psychology - Benjamin E. Hilbig (<>: New York : Elsevier : Orlando, Fla. : Academic Press)